A Review on Karir (Capparis Decidua Forssk.) An Ethno-Botanical Plant of Rajasthan - Bishnoi, Rameshwar lal; Kumar, Eresh; Kumar, Mukesh; Sharma, Ashwini Kumar; soni, Pradeep (International Research Journal of Ayurveda & Yoga, 2023)
In India, there are countless medicinal plants that are employed in numerous ancient medical practises. Individually or in combination, these plants have a huge potential to provide direct therapeutic benefit. The use of medicinal plants in modern medicine is expanding. In Ayurvedic and classical texts like the Charaka Samhita and the Sushruta Samhita, more than 70% of the medications are of herbal origin .Plants are used to treat a variety of diseases, including toothaches, coughs, and asthma, and have a greater range of applications in traditional folk medicine. All investigations showed that the plant has important pharmacological properties such as anti inflammatory, analgesic, anti-microbial, anti-plaque, anti-hypertensive, and anti-helmintic properties.It is also renowned for being an abundant source of glycosides, phenols, sterols, and alkaloids. In Rajasthan and other places, C. decidua (Karir) has shown to be a plant with significant commercial value. It offers numerous dietary and medical applications; it is important to synthesise a thorough study of connected topics. Because of this, the current review text concentrates on a thorough profile of important nutrients and biochemical molecules as well as the medical benefits of these substances. To evaluate the nutritional and medical significance of C. decidua, an effort is undertaken to study numerous studies on the plant. Furthermore, prior findings still need to be scientifically validated.